Between Coal Power Generation and Renewable Energy: A Review of Investment Aspects - Rayza Pranadipa; Zulkifli Sulton (CV. Rayyan Dwi Bharata, 2022)
This paper aims to analyze the growth of steam power plants and renewable energy reviewed with investment. This research uses a descriptive quantitative method with secondary data, namely the report of the Ministry of Energy and Mineral Resources and the Electricity Supply Business Plan. The results of this study found that the total renewable energy capacity and renewable energy investment did not increase significantly, temporarily. Total coal-fired power plant capacity, electrical energy consumption and coal sales for electricity production increased significantly.